Studies on the Root Characteristics of Maize Varieties of Different Eras - Feng-lu ZHANG; Xing-kui NIU; Yi-ming ZHANG; Rui-zhi XIE; Xin LIU; Shao-kun LI; Shi-ju GAO (Journal of Integrative Agriculture, 2013)
Experiment was conducted at the Gongzhuling Experimental Station of Institute of Crop Sciences, Chinese Academy of Agricultural Sciences, Jilin Province, China, during 2009–2010. Six representative varieties of maize (Baihe in the 1950s, Jidan 101 in the 1960s, Zhongdan 2 in the 1970s, Yedan 13 in the 1980s, Zhengdan 958 in the 1990s, and Xianyu 335 in the 2000s) were each planted under two different densities (52 500 and 82 500 plants ha−1) and two different nitrogen application levels (150 and 300 kg ha−1). Root characteristics and distribution among soil layers were studied by the field root digging method. The results showed that root mass increased with the process of the growth and development of the plant, and it peaked at kernel filling stage, and decreased at maturity due to the root senesces. Root mass of different maize varieties from the 1950s to 1980s had a trend of increase, while it decreased for the modern varieties. Root length and root surface areas had the similar changing trend. The study suggested that early maize varieties may have root redundancy, and reducing root redundancy may be a direction for variety improvement for high yield. Root characteristics were affected by nitrogen application level and density; modern varieties were more suitable for higher fertilizer application level and density conditions. Root characteristics distribution among soil layers decreased by an exponent equation, but the regression coefficients of different varieties were different. Though the root length density (RLD) of every soil layer of different varieties also decreased by an exponent equation, there were large variations of RLD in every part of a layer.